A coerência e a coesão nas redações dos alunos do ensino médio sob a perspectiva da lingüística sistêmico-funcional - Orlando, Maria Célia da Silva (2008)
This study aims to investigate argumentative essays written by second grade students attending the first year of evening classes in a public high school in Sao Paulo. The factors which have led me to do this research are two: the proposal made by the State Secretary of Education through the necessity to rise the level of the test grades administered by the School Achievement Assessment System of the State of Sao Paulo (SARESP), and students concern to improve their writing skills so as to get into university and the labor market. The corpus of this research consists of 70 argumentative essays, two of which have been chosen for the analysis. The criteria used for the analysis are recentness and sameness of theme. For the analysis of the data of this qualitative study we have drawn upon the Systemic Functional Linguistics of Halliday & Hasan (1976), Halliday & Hasan (1989) and Eggins (1994), as well as on more recent researches which have enriched the notions of cohesion and coherence. Thus, as far as text coherence is concerned, its analysis has been carried out by taking into account the notions of cultural and situational contexts. The analysis of text cohesion, on the other hand, has been made by observing lexical choice, maintenance of participants and use of conjunctions. The results have shown that the non-observance of those criteria may explain why the texts examined lacked both coherence and cohesion, which affects the argumentative effect desired by the author